STUDI DESKRIPTIF PERUBAHAN LEMAK SUBKUTAN SETELAH LATIHAN FISIK INTENSITAS MODERAT - Heru Syarli Lesmana; Padli Padli (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2019)
Accumulation of fat that occurs because of the imbalance of energy entering and excreting the human body causes obesity. The effort that can be done to eliminate fat is doing moderate intensity physical exercise which will make fat as energy. This study aims to describe descriptively changes in fat after moderate intensity physical exercise. 11 University Students of the Faculty of Sport Sciences who meet the criteria of inquiry, men, ages 19-20 years, ideal body weight according to BMI (Body Mass Index), willing to follow the research protocol and healthy selected as samples. The sample performed moderate intensity running exercise with a target heartrate 70% from the maximum heartrate controlled using the Heart Rate Monitor (Polar). Subcutaneous fat was measured on the body, legs and arms using the Omron Body Fat Monitor HBF-375 before and after exercising. The results showed a mean decrease in subcutaneous fat in the body, hands and feet decreased after physical exercise.